2018
DOI: 10.1371/journal.pone.0207656
|View full text |Cite
|
Sign up to set email alerts
|

Impact of "test and treat" recommendations on eligibility for antiretroviral treatment: Cross sectional population survey data from three high HIV prevalence countries

Abstract: BackgroundLatest WHO guidelines recommend starting HIV-positive individuals on antiretroviral therapy treatment (ART) regardless of CD4 count. We assessed additional impact of adopting new WHO guidelines.MethodsWe used data of individuals aged 15–59 years from three HIV population surveys conducted in 2012 (Kenya) and 2013 (Malawi and South Africa). Individuals were interviewed at home followed by rapid HIV and CD4 testing if tested HIV-positive. HIV-positive individuals were classified as “eligible for ART” i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…As such, the observed higher sensitivity during 2011–2012 than in 2007–2010 are expected. The 2013–2018 period saw major changes in national HIV/ART guidelines including expansion of Option B+ [ 18 , 19 ] to all antenatal care clinics in Malawi in 2013 [ 20 , 21 ], and adoption of the 2015 WHO guidelines [ 22 ] on universal ‘test and treat’ in 2016 [ 23 25 ]. It might be expected that more people would be aware of their HIV status during this period resulting in higher sensitivity for HIV status.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the observed higher sensitivity during 2011–2012 than in 2007–2010 are expected. The 2013–2018 period saw major changes in national HIV/ART guidelines including expansion of Option B+ [ 18 , 19 ] to all antenatal care clinics in Malawi in 2013 [ 20 , 21 ], and adoption of the 2015 WHO guidelines [ 22 ] on universal ‘test and treat’ in 2016 [ 23 25 ]. It might be expected that more people would be aware of their HIV status during this period resulting in higher sensitivity for HIV status.…”
Section: Discussionmentioning
confidence: 99%
“…For minors younger than 18 years, parental/guardian consent was sought first in Ndhiwa (Kenya) and Eshowe (South Africa) but was not required in Chiradzulu (Malawi) where minors aged 14-17 years old are considered able to give their own consent for HIV testing. Details of HIV rapid testing methods and other laboratory tests carried out including testing materials have been reported in more detail elsewhere [20]. Data were double entered using EpiData and checked for inconsistencies before analysis.…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…Detailed description of the demographic characteristics of the study population has been reported elsewhere [20]. For this analysis, we compared the characteristics of PLHIV with and without advanced HIV disease using chi-square tests.…”
Section: Statistical Methods and Analysismentioning
confidence: 99%
“…To date, studies on whether HIV "Treat All" has improved ART initiation among adolescents are inconclusive. Positive effects have been shown in some studies, while others have shown that they are still at risk of not initiating ART [23,[27][28][29]. To our knowledge, no evidence-based strategies are currently being implemented in Zimbabwe on a broader scale under "Treat All" to promote ART initiation among adolescents and young adults.…”
Section: Plos Onementioning
confidence: 99%